Hard X-ray beam damage study of monolayer Ni islands using SX-STM. Issue 1754 (2015) - Shirato, Nozomi; Cummings, Marvin; Kersell, Heath; Li, Yang; Miller, Dean; Rosenmann, Daniel; Hla, Saw-Wai; Rose, Volker
ABSTRACT: X-ray beam-induced damage in nanoscale metal islands was investigated. Monolayer-high Ni islands were prepared on a Cu(111) substrate. High brilliance X-rays with photon energies between 8.45 and 8.85 keV illuminated the sample for about 11 hours. In order to track changes in the morphology of the islands, the synchrotron X-ray scanning tunneling microscopy (SX-STM) technique was utilized. The result shows that X-ray illumination onto Ni islands does not induce noticeable damage. The study demonstrates that local beam-induced changes can be studied using SX-STM.